The Ten-Step Program for Planning and Preparation To Diminish the Agricultural Terrorism Threat Based Upon Planning Activities and Preparedness Exercises In The Texas Panhandle - Hueston, Harry R.; DeOtte, Robert E. (Journal of Agricultural Systems, Technology, and Management, 2007)
Agroterrorism, or terrorism against agricultural targets or using agricultural products, remains a viable threat to America. Yet few regional or local agricultural industries have reviewed existing state plans and considered applications to their localities or regions. Although state and federal officials may have confidence in their preparation, much work remains for the local and regional levels in order to prevent an attack or mitigate the consequences. A ten-step program, based upon regional experience and several readiness exercises, prepares local and agricultural leaders for their roles in preventing or handling future attacks. The program developed for the Texas Panhandle is readily applicable for any region with large concentrations of livestock. Evidence of the utility of this program is apparent in the progression of preparedness traced through several exercises and by application during the largest one-day wildfire in the history of the United States in March 2006.